An integrated approach for understanding the factors that facilitate or constrain the adoption of soil carbon enhancing practices in East Africa, Kenya and Ethiopia - Karanja Ng'ang'a, Stanley; Gelaw, Fekadu; Nguru, Wilson Maina; Magambo Kanyenji, George; Girvetz, Evan Hartunian (International Center for Tropical Agriculture, 2019)
The survey data on soil carbon enhancing practices in Ethiopia is systematically organized in Microsoft Excel tables. The data entails general household characteristics, plot characteristics, crops grown, yield, practices implemented, inputs, livestock ownership, social capital, access to credit, access to extension services.